Predictors of depressive symptoms in older adults living in care homes in Thailand - Tosangwarn, Suhathai; Clissett, Philip; Blake, Holly (2016)
Background: Most Thai people reject the idea of letting their ageing parents live in a care home due to the belief that a care home is a place for poor older adults who have no family. These beliefs could influence the perception of living in a care home among older residents and result in low self-esteem, isolation, self-harm and depression. Therefore, this study explored the factors associated with depressive symptoms and other variables among older adults residing in a care home in Thailand. Method/Design: 128 older residents were recruited from two care homes in the northeast of Thailand and data was collected using the 15-Item Thai Geriatric Depression Scale, Internalised Stigma of Living in a Care Home Scale, Thai Version of Rosenberg Self-Esteem Scale, Thai Version of Multidimensional Scale of Perceived Social Support and a Coping Strategies Inventory Short Form. Results: Depressive symptoms were found to be significantly correlated with internalised stigma, self-esteem and social support (r= 0.563, -0.574 and -0.333) (p< 0.001), respectively. Perceived internalised stigma of living in a care home is the strongest predictor of reporting experiencing some level of depressive symptoms, resulting in an odds ratio of 9.165. Discussion: Perceived internalised stigma is significantly positively correlated with depressive symptoms and is the strongest predictor of the risk of depressive symptoms. By understanding and improving the knowledge of internalised stigma of living in a care home could inform strategy, intervention and guidelines for appropriate care for older adults residing in a care home.